2015
DOI: 10.3390/s150716895
|View full text |Cite
|
Sign up to set email alerts
|

Medium to Long Range Kinematic GPS Positioning with Position-Velocity-Acceleration Model Using Multiple Reference Stations

Abstract: In order to obtain precise kinematic global positioning systems (GPS) in medium to large scale networks, the atmospheric effects from tropospheric and ionospheric delays need to be properly modeled and estimated. It is also preferable to use multiple reference stations to improve the reliability of the solutions. In this study, GPS kinematic positioning algorithms are developed for the medium to large-scale network based on the position-velocity-acceleration model. Hence, the algorithm can perform even in case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…The survey was flown by Cessna Grand Caravan at speeds of about 280 km/h and a constant altitude of 10,000 feet. GPS data were collected from both GPS receivers and six ground-based continuously operating reference stations (CORS) at an interval of 1 s. GPS measurements were collected using both receivers connected to a single antenna with the kinematic accelerations of the aircraft being computed using the network-based PVA model proposed by [ 6 ]. Figure 2 shows the 1.5 h span (~400 km in distance) of 1 htz GPS data collected on 11 January 2009 that were selected for this study.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey was flown by Cessna Grand Caravan at speeds of about 280 km/h and a constant altitude of 10,000 feet. GPS data were collected from both GPS receivers and six ground-based continuously operating reference stations (CORS) at an interval of 1 s. GPS measurements were collected using both receivers connected to a single antenna with the kinematic accelerations of the aircraft being computed using the network-based PVA model proposed by [ 6 ]. Figure 2 shows the 1.5 h span (~400 km in distance) of 1 htz GPS data collected on 11 January 2009 that were selected for this study.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Also, the corresponding transition matrix, which describes the dynamic of aircraft and GPS measurement model, is constructed for medium- to long-range kinematic applications. More details on the PVA model and the approaches adopted in this study can be found in [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance analysis and reference values of the reported algorithms were confirmed by comparing the results. The results show that reliable and similar solutions can be obtained at the position and kinematic acceleration levels using the proposed algorithms [ 40 ].…”
Section: Organization Of the Iot Applicationsmentioning
confidence: 86%
“…IoT cihazlar izleme, konfor ve güvenliği artırmak amacıyla ev ve binalarda elektrik, elektronik ve mekanik sistemleri kontrol etmek için kullanılmaktadır (Jiang, et al;. Binalarda kullanılan sensörler köprüde kullanılanlar gibi binaların yapısal durumunu gözlemlemektedir (Hong, et al;2015. Yine sensörler sayesinde deprem sonrasında oluşan çatlaklar sonucu binaların acil olarak boşaltılması sağlanmakta ve deprem sonrasında binanın kayıp kaymadığı hesaplanabilmektedir (Ahmad, et al;.…”
Section: 1)ev Ve Bina Otomasyonunda Iotunclassified